Interest rate derivatives use in banking: Market pricing implications of cash flow hedges - Akhigbe, Aigbe; Makar, Stephen; Wang, Li; Whyte, Ann Marie (Journal of Banking & Finance, 2018)
We examine whether investors are able to fully anticipate the pricing implications of cash flow hedges in the banking industry. We show that mark-to-market adjustments on cash flow hedges are inversely related to future cash flows and that investors underestimate the extent of this inverse relation. Our evidence supports the notion that incomplete information on value relevant parameters makes it difficult for investors to accurately predict the effects of current cash flow hedge adjustments on future cash flows. Our results are also consistent with the evidence that investors have limited attention such that information, particularly information that is difficult to discern, is not fully reflected in stock prices. Thus, the additional disclosures mandated by regulatory agencies in the banking industry are not sufficient to overcome the challenges associated with incomplete information and investors’ limited attention.